Synchronous Seasonality in the Gut Microbiota of Wild Mouse Populations - Marsh, Kirsty J.; Raulo, Aura M.; Brouard, Marc; Troitsky, Tanya; English, Holly M.; Allen, Bryony; Raval, Rohan; Venkatesan, Saudamini; Pedersen, Amy B.; Webster, Joanne P.; Knowles, Sarah C. L. (Frontiers in Microbiology, 2022)
The gut microbiome performs many important functions in mammalian hosts, with community composition shaping its functional role. However, what factors drive individual microbiota variation in wild animals and to what extent these are predictable or idiosyncratic across populations remains poorly understood. Here, we use a multi-population dataset from a common rodent species (the wood mouse, Apodemus sylvaticus), to test whether a consistent set of ‘core’ gut microbes is identifiable in this species, and to what extent the predictors of microbiota variation are consistent across populations. Between 2014 and 2018 we used capture-mark-recapture and 16S rRNA profiling to intensively monitor two wild UK mouse populations and their gut microbiota, as well as characterising the microbiota from a laboratory-housed colony of the same species. Although broadly similar at high taxonomic levels and despite being only 50km apart, the two wild populations did not share a single bacterial amplicon sequence variant (ASV). Meanwhile, the laboratory-housed colony shared many ASVs with one of the wild populations from which it is thought to have been founded decades ago. Despite clear taxonomic divergence in the microbiota, the two wild populations shared a phylogenetically more similar microbiota than either did with the colony, and the factors predicting compositional variation in each wild population were remarkably similar. We identified a strong and consistent pattern of seasonal microbiota restructuring that occurred at both sites, in all years, and within individual mice. While the microbiota was highly individualised, some seasonal convergence among individuals’ gut microbiota occurred in late winter/early spring. These findings reveal highly repeatable seasonal gut microbiota dynamics in multiple populations of this species, despite divergent taxa being involved. This provides a platform for future work to understand the drivers and functional implications of such predictable seasonal microbiome restructuring, including whether it might provide the host with adaptive seasonal phenotypic plasticity.